PENGARUH PENGGUNAAN MODEL PEMBELAJARAN RECIPROCAL TEACHING TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATA PELAJARAN EKONOMI KELAS X SMA NEGERI 4 CIREBON - Rifela Sri Hendayani (Edulead : Journal of Education Management, 2019)
The aims of the study are to determine the response of students to learning Economic using reciprocal teaching learning model, determine differences in cognitive learning outcomes of students in class who use reciprocal teaching learning models with students in the class that uses the lecture model, and know the influence of reciprocal teaching learning model of cognitive learning outcomes of students in the Economics subjects. The study uses quasi-experimental and data collection techniques use the test to determine the effect of reciprocal teaching learning model for cognitive learning outcomes of students in the Economics subject and differences in cognitive learning outcomes of students in the class are using reciprocal teaching learning model with participants students in the class that uses the model of lecture and use a questionnaire to determine the students’ response to learn Economic using reciprocal teaching learning model. The populations are students of class X in SMA Negeri 4 Cirebon are 324 learners. The samples were taken by using simple random sampling technique. The sample in this study is X IIS 1 as an experimental class and X IIS 3 as the control class. The results showed that the class using reciprocal teaching of learning models on the Economics subjects in SMA Negeri 4 Cirebon gets an average value of 82,08. Mean while, the class who did not use reciprocal teaching of learning models gets the average value of 77,08 .The results of hypothesis testing is tcount<ttable (-4,019 <-1,99444) there fore Ho is rejected and Ha is accepted, it’s mean that there are differences in cognitive learning outcomes of students between the experimental class and control class.The average gain of 0,61 obtained experimental class (medium category), and the average gain of 0,54 obtained control class (medium category).Thus, cognitive learning outcomes of students in the experimental class of Economy subjects better than the control class. Based on the regression coefficients X t values obtained arithmetic ≥ t table or ≥ 5,834 1,99444 then Ha is accepted, meaning that the use of reciprocal teaching of learning models significant effect on the value of cognitive learning outcomes of students. Based on this study, the reciprocal teaching learning model can be an option for teachers in implementing the learning so that learners Economic easier to understand the material being taught. Abstrak Penelitian ini bertujuan untuk mengetahui respon peserta didik terhadap pembelajaran Ekonomi dengan menggunakan model pembelajaran reciprocal teaching, mengetahui perbedaan hasil belajar kognitif peserta didik dikelas yang menggunakan model pembelajaran reciprocal teaching dengan peserta didik di kelas yang menggunakan model ceramah, dan mengetahui pengaruh penggunaan model pembelajaran reciprocal teaching terhadap hasil belajar kognitif peserta didik pada mata pelajaran Ekonomi. Metode yang digunakan dalam penelitian ini adalah eksperimen semu dan teknik pengumpulan data menggunakan tes untuk mengetahui pengaruh penggunaan model pembelajaran reciprocal teaching terhadap hasil belajar kognitif peserta didik pada mata pelajaran Ekonomi dan perbedaan hasil belajar kognitif peserta didik di kelas yang menggunakan model pembelajaran reciprocal teaching dengan peserta didik di kelas yang menggunakan model ceramah serta menggunakan angket untuk mengetahui respon peserta didik terhadap pembelajaran Ekonomi dengan menggunakan model pembelajaran reciprocal teaching. Pupolasinya adalah peserta didik kelas X di SMAN 4 Cirebon berjumlah 324 peserta didik. Sampel yang diambil dengan menggunakan teknik simple random sampling. Sampel dalam penelitian ini adalah X IIS 1 sebagai kelas eksperimen dan X IIS 3 sebagai kelas kontrol. Hasil penelitian menunjukan bahwa kelas yang menggunakan model pembelajaran reciprocal teaching pada mata pelajaran Ekonomi di SMAN 4 Cirebon mendapatkan nilai rata-rata 82,08. Sedangkan, nilai rata-rata 77,08 di kelas yang tidak menggunakan model pembelajaran reciprocal teaching. Dilihat dari hasil uji hipotesis di dapat -thitung<-ttabel (-4,019<-1,99444) dengan demikian Ho ditolak dan Ha diterima, artinya terdapat perbedaan hasil belajar kognitif peserta didik antara kelas eksperimen dan kelas kontrol. Rata-rata gain kelas eksperimen didapatkan 0,61 (kategori sedang), dan rata-rata gain kelas kontrol didapatkan 0,54 (kategori sedang). Dengan demikian, hasil belajar kognitif peserta didik pada mata pelajaran Ekonomi kelas eksperimen lebih baik dari kelas kontrol. Berdasarkan koefisien regresi X diperoleh nilai thitung ≥ ttabel atau 5,834 ≥ 1,99444 maka Ha diterima, artinya penggunaan model pembelajaran reciprocal teaching berpengaruh signifikan terhadap nilai hasil belajar kognitif peserta didik. Berdasarkan penelitian ini, maka model pembelajaran reciprocal teaching dapat dijadikan pilihan bagi guru dalam melaksanakan pembelajaran Ekonomi agar peserta didik lebih mudah untuk memahami materi yang diajarkan.